THE EFFECT OF CURRENT RATIO (CR) AND DEBT TO EQUITY RATIO (DER) ON RETURN ON ASSETS (ROA) IN ENERGY SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2020–2024 - Utina, Almuhajir Baihaqy; Noholo, Sahmin; Husain, Siti Pratiwi (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the effect of Current Ratio (CR) and Debt to Equity Ratio (DER) on Return on Assets (ROA) in energy sector companies listed on the Indonesia Stock Exchange during the period 2020–2024. The research method employed is a quantitative approach with a causal associative design. The data used are secondary data obtained from companies’ financial statements, with a total sample of 110 observations. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 26. The results show that partially, the Current Ratio (CR) has no significant effect on Return on Assets (ROA), with a significance value of 0.833. Meanwhile, the Debt to Equity Ratio (DER) has a negative and significant effect on Return on Assets (ROA), with a significance value of 0.000. Simultaneously, Current Ratio (CR) and Debt to Equity Ratio (DER) have a significant effect on Return on Assets (ROA), as indicated by an F-test significance value of 0.000. The coefficient of determination (Adjusted R Square) of 0.128 indicates that the independent variables explain 12.8% of the variation in ROA, while the remaining 87.2% is influenced by other factors outside the research model. This study concludes that capital structure plays a more dominant role in influencing profitability compared to liquidity in energy sector companies. Therefore, companies are expected to manage debt usage optimally to improve financial performance.